(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION: Diabetes is a metabolic disease characterized by hyperglycemia, with high morbidity and mortality worldwide. The micro-vascular complications of Diabetes Mellitus, are considered as an important part of hyperglycemia limitations, caused by the increased endothelial permeability and can progress to severe impairments in several organ systems. AIM: To analyse correlation of microvascular complication with period of diabetes mellitus, glycemic control and hypertension. METHOD: A study of 100 patients with DM were included with age ranging from 20 to 80 years. CONCLUSION: Diabetic retinopathy was the most common late complication observed in the study. Diabetic retinopathy, neuropathy and nephropathy all are associated with poor glycemic control. Long duration of DM, with poor glycemic control and the associated hypertension all increase the chances of micro-vascular complications in DM.